Nursing Skill Assessment of Hospital Nurses in Management of Critically Ill Patients - Lingli Xu; Qiyu Sun; Jiayi Feng; Li Jing Huang; Chunjing Xu; Weihong Shen; Jian Ding; Yongmei Jin (Applied Bionics and Biomechanics)
Objective. To analyze the application of standardized nursing procedures in critically ill patients’ nursing evaluation. Methods. 90 cases of critically ill patients aged from 18 to 65 who were treated in our hospital from April 2020 to April 2021 were selected and divided into the control group and observation group, respectively, with 45 cases according to the drawing method. The rescue time, blood pressure, heart rate before and after nursing, adverse mood, length of stay, incidence of adverse events, ICU transfer and death, and satisfaction of 2 groups were statistically analyzed and compared. Results. The rescue time of cardiopulmonary resuscitation, oxygen inhalation, venous opening, and endotracheal resuscitation in the observation group was 3.24±1.01, which is lower than that in the control group, 6.65±2.11, with statistical significance (P<0.05). Similarly, the vital signs in the observation group were 2.45±0.44, which is also significantly lower than that in the control group, 5.67±1.56. After nursing, the blood pressure and heart rate in the observation group were lower than those in control group, with statistical significance (P<0.05). The adverse mood of the observation group after nursing was lower than that of the control group, with statistical significance (P<0.05). The length of stay, incidence of adverse events, intensive care unit (ICU) transfer, and death in the observation group were lower than those in the control group, with statistical significance (P<0.05). The length of stay in the observation group was 8.87±2.11, while 11.34±2.45 in the observation group. The incidence of adverse events in the observation group was 1, while 8 in the observation group. The length of stay in the observation group was 8.87±2.11, while 11.34±2.45 in the observation group. The ICU transfer in the observation group were 2, while 9 in the observation group. There was no death in the observation group, however, 4 in the observation group. Nursing satisfaction in the observation group was higher than that in the control group, with statistical significance (P<0.05). The number of patients that are very satisfied in the observation group was 28, while 20 in the control group. The number of patients that are satisfied in the observation group was the same as in the control group, both 15. However, the number of patients that are dissatisfied in the observation group was 2, while 10 in the control group. Conclusion. The application of the standardized nursing process in the nursing of critically ill patients can not only effectively reduce the self-rating anxiety scale (SAS) and sarcoidosis diagnostic score (SDS) of patients but also reduce the incidence of complications and improve the nursing satisfaction of patients.